Pluralisme Hukum dalam Lembaga Perkawinan: Persinggungan Norma Islam dan Norma Adat dalam Mengatur Perkawinan dan Harta Kekayaan di Toraja Utara: The Intersection of National Law, Islamic Law, and Customary Law in Regulating Marriage and Common Property in North Toraja - Akbar, Alif; Laman, Ilham (Universitas Islam Negeri Alauddin Makassar, 2025)
This research aims to explore how the two legal systems interact, experience tension, and are negotiated in the social practices of society. Legal pluralism in Indonesia shows the existence of various systems of state norms, Islamic law, and customary law that coexist in one social space. In North Toraja, the Muslim community faces the intersecting dynamics between Islamic norms and Torajan customs in regulating marriage institutions and wealth management. This research uses a socio-legal approach with a descriptive qualitative method. Data were collected through field observations, in-depth interviews with religious leaders, traditional leaders, married couples, and legal practitioners, and documentation studies of customary texts and marriage documents. The analysis was carried out thematically to identify patterns of integration, compromise, and conflict between Islamic norms and customs. The results of the study show that Islamic law forms a formal framework in the implementation of marriage contracts and dowry arrangements, while customary law remains dominant in determining social legitimacy, customary rituals, and distribution of family wealth. In conflict resolution, the community prioritizes informal customary mechanisms, while the principles of Islamic law are applied selectively, especially when dealing with state legal institutions. This study confirms the existence of adaptive strategies used by the community in responding to the plurality of laws. The intersection between Islamic law and customary law is not confrontational, but rather forms a functional and contextual hybrid legal culture. The novelty of this research lies in the documentation of the practice of legal syncretism in the context of Muslim marriage in the Toraja customary environment, as well as its relevance in formulating legal policies that are more inclusive of local social and cultural realities.